2017
DOI: 10.1590/1980-5373-mr-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Co-Ni/SiC Nanocomposite Coating Obtained by Electrodeposition on the Corrosion Resistance of API 5L X80 Steel

Abstract: Co-Ni/SiC nanocomposite coatings were obtained by codeposition of SiC nanoparticles in a bath with nickel and cobalt, using API 5L X80 as the substrate. The influence of cathodic current density on deposit properties was investigated. Measurements of electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PP) were performed in 3.5 wt% NaCl solution to investigate a corrosion performance. The morphology and chemical analysis of the surfaces were analyzed by scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The behavior observed between the micro-hardness values and the SiC content of the samples surface was similar to that observed by Pereira et al, who associated the micro-hardness with the nanoparticulate SiC content in Co-Ni/SiC nanocomposite coating electrodeposited in API 5L X80 steel 16 . Bakhit analyzed the influence of the SiC particle size on the nanocomposite structure and tribological properties and found that increasing the concentration of SiC particles incorporated in the Ni-Co nanocomposite results in increased micro-hardness 36 .…”
Section: Micro-hardnesssupporting
confidence: 87%
See 3 more Smart Citations
“…The behavior observed between the micro-hardness values and the SiC content of the samples surface was similar to that observed by Pereira et al, who associated the micro-hardness with the nanoparticulate SiC content in Co-Ni/SiC nanocomposite coating electrodeposited in API 5L X80 steel 16 . Bakhit analyzed the influence of the SiC particle size on the nanocomposite structure and tribological properties and found that increasing the concentration of SiC particles incorporated in the Ni-Co nanocomposite results in increased micro-hardness 36 .…”
Section: Micro-hardnesssupporting
confidence: 87%
“…The coatings were obtained by galvanostatic deposition technique using a single bath and a single cathodic current density value (5.5 A dm -2 ). The cathodic current density value was defined by a previous study and corresponded to the current condition, wich was able to obtain the coating with the best properties for this system 16 . The bath pH was maintained at 4.5, it was adjusted with NH 4 OH or H 2 SO 4 when necessary 7 .…”
Section: Electrolyte and Electrodepositing Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [16] reported that the wear resistance of NiCo film is higher than the pure Ni one. Pereira et al [17] researched the corrosion resistance characteristics of NiCo film deposited on a steel surface. However, the structure transformation and deformation behaviours of the NiCo film still needs further study to shed more light on its structure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%